2015
DOI: 10.7554/elife.10721
|View full text |Cite
|
Sign up to set email alerts
|

Filopodial dynamics and growth cone stabilization in Drosophila visual circuit development

Abstract: Filopodial dynamics are thought to control growth cone guidance, but the types and roles of growth cone dynamics underlying neural circuit assembly in a living brain are largely unknown. To address this issue, we have developed long-term, continuous, fast and high-resolution imaging of growth cone dynamics from axon growth to synapse formation in cultured Drosophila brains. Using R7 photoreceptor neurons as a model we show that >90% of the growth cone filopodia exhibit fast, stochastic dynamics that persist de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 47 publications
4
93
0
Order By: Relevance
“…This system is similar to one developed by Hiesinger and colleagues to study the cellular mechanism of neural superposition, the choreographed re-distribution of R1-6 growth cones from ommaditial bundles to lamina cartridges (Langen et al, 2015). In the medulla neuropil, Hiesinger and colleagues used ex vivo live imaging to study R7 targeting, specifically characterizing the role of the Ca2+-dependent cell adhesion molecule, N-cadherin, in mediating adhesive interaction between growth cones and the developing neuropil (Özel et al, 2015).
Video 1.Medulla Registration.The developmental roll of the medulla is corrected in preparation for growth cone segmentation and tracking. DOI: http://dx.doi.org/10.7554/eLife.20762.007
…”
Section: Resultsmentioning
confidence: 99%
“…This system is similar to one developed by Hiesinger and colleagues to study the cellular mechanism of neural superposition, the choreographed re-distribution of R1-6 growth cones from ommaditial bundles to lamina cartridges (Langen et al, 2015). In the medulla neuropil, Hiesinger and colleagues used ex vivo live imaging to study R7 targeting, specifically characterizing the role of the Ca2+-dependent cell adhesion molecule, N-cadherin, in mediating adhesive interaction between growth cones and the developing neuropil (Özel et al, 2015).
Video 1.Medulla Registration.The developmental roll of the medulla is corrected in preparation for growth cone segmentation and tracking. DOI: http://dx.doi.org/10.7554/eLife.20762.007
…”
Section: Resultsmentioning
confidence: 99%
“…We, therefore wondered how DRA.R7 and DRA.R8 cells could reliably choose between different post-synaptic partners when terminating in such close proximity within their respective M6 sublayers. In order to get some insight into this process, we decided to characterize the time series of DRA.R8 photoreceptor axons growing into the medulla, using 2-photon live imaging 42 (see material and methods) ( Figure 7A, Supplemental Movie 3). Imaging sparsely labeled R7 and/or R8 cells (within the DRA and outside of it) from an ex vivo brain explant over the course of 18 hours revealed the temporal dynamics of their individual outgrowth behavior during layer targeting ( Figure 7B).…”
Section: Sequential Targeting Of Drar7 and Drar8 Photoreceptor Termmentioning
confidence: 99%
“…To achieve this DRA-specific connectivity, polarizationsensitive DRA.R8 cells differ from their color-sensitive counterparts both in layer targeting and the distribution of their presynaptic sites. Finally, using live imaging of ingrowing photoreceptor axons 42 , we visualize the temporal sequence of R7 and R8 axons targeting to the M6 layer, thereby temporally separating synaptic partner choices. Our work reveals an instance for how repetitive microcircuits, organized in highly stereotypical medulla columns, can become reorganized locally in order to adapt them to their modality-specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…3B). R7 growth cones never actively extend thereafter, forming early contacts with their main postsynaptic partners, Dm8; new layers form through intercalations between these early R8 and R7 layers [32,43] (Fig. 3B).…”
Section: The Role Of Layers and Laminae For Synaptic Specificationmentioning
confidence: 99%
“…The role of N-cadherin is often interpreted as ‘broadly adhesive’ and functioning redundantly with other factors, in part because mutant neurons often target correctly during early development [1,9,39]. However, R7 live imaging revealed that cadN mutant fly R7 axons actively jump between correct and incorrect medulla layers, arguing against a strict role for CadN in preferential adhesion within the correct layer [43]. Subsequent to its own targeting, L3 produces the secreted attractant netrin, which influences R8 growth cones as they actively extend to this same layer [48].…”
Section: The Role Of Layers and Laminae For Synaptic Specificationmentioning
confidence: 99%